Educating from the emotions: a teaching landscape in Chilean education - Cornejo Asmussen, Pablo (2019)
Educational settings are sustained by human relationships, established interpersonal activities, resolved conflictivesituations, promoting healthy bonds, the use of authority by teachers, emotional reading, acknowledging theother person beyond cognitive variables, the ability to listen and valuing empathy in different situations with thestudent that affect the school setting. All of these factors depend on, among other things, the socio-emotionalcompetence of the adult who plays a teaching role and they are linked with students’ motivation in regardsto learning and academic performance. The aim of this manuscript is to give a panoramic view of the currenteducational viewpoint, teachers’ mental health, establish the importance of emotional education as well as theuse of positive psychology as a paradigm in schools. Lastly, the involvement of emotional education and positivepsychology in an educational setting is discussed.